Harmonic series experiments: end-correction factor of the Indonesian Angklung - Anis Nazihah binti Mat Daud (Tanjung Malim, 2024)
Harmonic series experiments: end-correction factor of the Indonesian Angklung by Anis Nazihah binti Mat Daud